Naturalism in August Strindberg's Miss Julie - Nadia Kumari; Steffani Trifena Napitupulu; Syifa Inayah Hanani Zulfa; Syamsul Bahri (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
Naturalism is a literary movement that emerged in the late 19th century to portray life with scientific precision, emphasizing the influence of heredity, environment, and socio-economic conditions on human behavior. In drama, this approach offers a stark and unfiltered depiction of human struggles within oppressive social systems. This study aims to explore August Strindberg's Miss Julie through the lens of naturalism, specifically using Vernon L. Parrington’s seven characteristics of the movement: Objectivity, Frankness, An Amoral Toward Material, Determinism, Inclination Toward Negativity in Choice of Detail, Characters Are Liable to Specific Enticements and Pessimism. Employing a descriptive qualitative method, the research analyzes selected dialogues from the play to identify naturalist elements. The findings reveal that Miss Julie strongly embodies all seven aspects, with a particularly dominant presence of negative detail (44%) and objectivity (20%). The discussion highlights how the characters’ actions are shaped by class conflict, psychological trauma, and instinctual drives, leading to tragic outcomes. Through its bleak realism and emotional depth, the play not only fulfills but also expands the boundaries of naturalist drama by dissecting themes of gender, power, and existential despair.